The Impact of Religiosity on Criminality - Ivanović, Miroslav (Zbornik Instituta za kriminološka i sociološka istraživanja, 2006)
We are considered the impact of religiosity on the criminality from functionalistic point of view. The empirical evidence collected in some researches was contadictory. The acceptable explanation is that the religiosity reduces criminality only inside so called “moral communities”, but it is not case in the secularized society. Nonfunctionality of religion is presented on the example of sects and in relation to it are formulated the basic problems.